(untitled) (Research, Society and Development, 2020)
This study aims to evaluate of Reichian Elongation effect in anxiety and quality of life in nursing students. This is a prospective randomized clinical trial (Registration: RBR-2y6qcg). 143 nursing students were interviewed. The General Identification, the State-Trait Anxiety Inventory (STAI), The World Health Organization Quality of Life (WHOQOL-BREF) and MINI (Mini International Neuropsychiatric Interview) questionnaires were used. 33 received the intervention and 37 belonged to the control group. The evaluation of the elongation effect was conducted by 1, 3 and 5 months. Before intervention, experimental group presented higher trait (p= 0.005) and state anxiety mean (p= 0.049), compared to control group. There was a decrease in the state anxiety mean with 1 (p= 0.028), 3 (p= 0.031) and 5 months (p= 0.010) in experimental group. Physical (p= 0.002), psychological (p= 0.010) and social relations domain (p= 0.026) showed an increase in quality of life. Reichian Elongation contributes in reducing the symptoms of anxiety and improving the students’ quality of life.